Hypertensive Disorder of Pregnancy with Vertebral Artery Aneurysm and Vasospasm Led to Vertebral Artery Dissection – A Case Report - Habib, SM Ahsanul; Sultana, Arifa; Rahim, Riffat; Alam, Mohammad Ashraful; Mohammad, Taneem (Mugda Medical College Journal, 2024)
Hypertensive disorders of pregnancy (HDP) can lead to various complications affecting maternal and fetal health. In this case report, we present the rare occurrence of vertebral artery aneurysm leading to vasospasm with vertebral artery dissection (VAD) in a woman having pregnancy-induced hypertensive disorder. Her clinical presentation, diagnostic evaluation, and management are discussed, highlighting the importance of early recognition and appropriate intervention. This case highlights the potential link between pregnancy-induced hypertensive disorders and a rare vascular complication like vertebral artery aneurysm which may lead to vertebral artery dissection. The current literature consists of a few incidences documenting adverse outcomes and management. The incidence of recurrence of such events (arterial aneurysms and dissection) in subsequent pregnancies is unknown. Timely recognition, appropriate diagnostic evaluation, and multidisciplinary collaboration are essential for optimal management and patient outcomes. Mugda Med Coll J. 2023; 6(2): 107-109